FEATURES OF REGIONAL BLOOD FLOW THIGH IN REPRESENTATIVES OF DIFFERENT SPORTS - Moroz, V.M.; Khapitska, O.P. (World of Medicine and Biology, 2016)
We determined the changes of time, amplitude and derivatives of these indicators rheovazograms of thigh at sportsmen of high level skills youth age engaged in volleyball, athletics and wrestling with sports experience at least three years. The control group made practically healthy persons aged 17-21 years. Installed significant differences in indicators of reovazograms of thigh in males youth age, depending on the impact of intense exercise. Sports specialization, which determines the features of muscle activity leads to changes in regional blood flow of thigh in representatives of various sports.
Keywords: regional bloodstream; rheovasography of thigh; volleyball players; athletes; wrestlers